Spectacular Island Tourism in Pulau Aman, Penang Malaysia: The Visitors’ Perspective - Normah Abdul Latip; Mohd Umzarulazijo Umar; Rehmat Karim; Mohamad Pirdaus Yusoh; Ang, Kean Hua; Johan Johnes; Rahmah Rashid (Malaysia Institute of Planners, 2023)
Island tourism initiative plays a significant role in uplifting economic activity for the island and local people. The equilibrium point of view between service providers and visitors is essential. Therefore, visitors’ perspective is crucial in understanding the need and requirement for establishment in tourist spots, including islands. This study examines visitors' perception of the study area through 3 main elements: activity, social and physical, comfortable, and natural beauty. The research design uses a descriptive analysis approach that uses a 5- point Likert scale, namely strongly agree (SA), agree (A), not sure (NS), disagree (D) and strongly disagree (SD). As for research analysis, the study used the SPSS program and specifically focused on frequency, mean, mode, median and level of agreement as to expected output. Preliminary findings indicate that visitors strongly agree that the area has the potential to be developed as a top tourism spot with minor improvement facilities and eco-tourism products.